Why are some public officials more corrupt than others? - Hunt, Jennifer (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 2005)
"Using detailed Peruvian data measuring bribery, I assess which types of public official are most corrupt and why. I distinguish between the bribery rate and the size of bribes received, and seek to explain the variation in each across public institutions. The characteristics of officials' clients explain most of the variation for bribery rates, but none for bribe amounts. A measure of the speed of honest service at the institution explains much of the remaining variation for both bribery rates and amounts. The results indicate that the bribery rate is higher at institutions with bribe-prone clients, and that bribery rates and bribe amounts are higher where clients are frustrated at slow service. Faster and better service would reduce corruption. Overall, the judiciary and the police are by far the most corrupt institutions"--National Bureau of Economic Research web site.